POWER OF POLICE (CIPEEX, 2025)
José dos Santos Carvalho Filho, in Chapter 3 of his Manual de Direito Administrativo (38th edition, 2024), explains the concept of police power as the State's ability to limit individual liberties and the use of property in the public interest. The author highlights that this power has a constitutional basis and must be exercised in accordance with the principles of legality, proportionality, and rationality. Furthermore, he emphasizes that police power differs from other state actions, as it involves the use of force in favor and service of the State to maintain its authority and preserve public order.